Creativity and cooking: Motherhood, agency and social change in everyday life. (March 2015) - McCabe, Maryann; de Waal Malefyt, Timothy
Creativity in the kitchen is a normal part of everyday life in US homes. This article explores improvisation by mothers in home cooking as exemplary of the creative process. Western analyses of creativity have typically examined innovation after-the-fact, and showed how something innovative constitutes something novel that is discontinuous with the past. This is reading creativity "backward" in terms of outcomes. We provide a "forward" reading of creativity that examines the conditions and constraints which give rise to improvisation. This offers insight into cooking as a form of personal and social creativity that is grounded in the familiar, and infused with cultural values of self-expression and pleasing the family. This article thus discusses how improvisation is shaped by individual agency and social structure. Creative behavior is limited yet inspired by the material, social and symbolic constraints of the context in which it occurs, including in this case the broader context of the politics of food. Our forward reading of creative cooking practices indicates how cultural production leads to social change through the mediation of agency and structure.